Habituation Of Language Politeness Of 2nd Grade Students Of MIS Sungai Baru Banjarmasin - Nora Najmi Azizah; Hafiz Mubarak (Interdisciplinary Explorations in Research Journal, 2023)
Habituation of language politeness used by school-age students is important. There are some students who still do not know or do not realize that the language they use is impolite. Many of them do not understand the manners in speaking to others. Therefore, teachers play an important role in the process of habituating students' language politeness. The purpose of this study is to describe the language politeness of grade 2 students of MIS Sungai Baru Banjarmasin and describe the role of teachers in habituating the language politeness of grade 2 students of MIS Sungai Baru Banjarmasin. This type of research is qualitative research in the form of describing data in the form of descriptive written or spoken words from the subjects and informants observed. The object under study is the language politeness of grade 2 students of MIS Sungai Baru Banjarmasin and the role of teachers in familiarizing students' language politeness. The subjects of this study consisted of the 2nd grade homeroom teacher, Arabic teacher, PJOK teacher, and 2nd grade students. The results of this study show that the form of language politeness of grade 2 students is the compliance and violation of language politeness consisting of maxims of generosity, maxims of appreciation, and maxims of simplicity. The role of the teacher in habituating students' language politeness includes strategies and gifts made in habituating the language politeness of grade 2 students of MIS Sungai Baru Banjarmasin.